Enhancing Mamanda Product Sales through Business Model Innovation (BMI) - Avanti Fontana; Isnaeni Kumalasari (Bina Nusantara University, 2024)
The research aimed to assist the micro-enterprise Mamanda in achieving sustainable improvements in product sales, addressing the challenges posed by the post-COVID-19 era. Operating in the children’s toy rental services field, Mamanda faced a significant decline in sales due to the pandemic’s impact on consumer behavior. The researchers collected data through interviews, meetings, and observations using qualitative methods and a business coaching approach. The analysis involved internal and external assessments, Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis, Business Model Canvas (BMC) evaluation, gap analysis, and Pareto analysis. From the results, the Pareto analysis identifies two critical issues: the lack of a customer database and the absence of a customer loyalty program. Business coaching effectively guides Mamanda in developing a new and adaptive business model to enhance sales sustainably in the post-COVID-19 landscape. Importantly, the research contributes to the literature by emphasizing key findings, highlighting the importance of adapting business models, effectively utilizing customer data, and implementing customer-centric strategies to foster growth and sustainability in the context of Micro, Small, and Medium Enterprises (MSMEs). Practical implications include the significance of Business Model Innovation (BMI) and customer-centric approaches for MSMEs in navigating evolving and competitive markets, ensuring resilience and viability in evolving business environments.